Comparing jury focus and comprehension of expert evidence between adversarial and court-appointed models in Canadian criminal court context. Issue 2 (2nd April 2020) - Smith, Rhonda L.; Kannemeyer, Maries; Adams, Emily; Nguyen, Vi Van; Munshaw, Ryot; Burr, Wesley S.
Abstract: The present adversarial system is often criticised for not working as well as it should in the area of expert scientific testimony. Yet scientific opinion evidence is an important aspect of present criminal trials. In addition to issues in the provision of expert evidence, triers of fact are challenged to understand complex scientific evidence. Several dynamics are at play that may impact on their ability to focus on and comprehend the science, and alternative models have been suggested to address these issues, including the use of court-appointed experts. This study examines juror focus on the science versus the persona/demeanour of the expert witness between the adversarial and court-appointed models for presentation of scientific evidence. Findings suggest that expert persona/demeanour continues to be a large focus area for jurors, that the CA model may be more resilient for ensuring greater focus on science, and that juror comprehension of science is somewhat better when presented via the court-appointed model. Results inform instruction of experts for giving opinion evidence as well as suggest the prudence of considering other models to improve the criminal justice system. Limitations as to the generalization of study results are discussed.